2007
DOI: 10.1590/s0103-97332007000600005
|View full text |Cite
|
Sign up to set email alerts
|

Space-time characterization and collective motion at intermediate energies

Abstract: Shape analyses of two-particle correlation functions are discussed. Two-proton imaging provides information about the volume, the relative contributions between fast and slow emitting sources and the profile of the twoparticle source that can be directly compared to microscopic model simulations. In the case of correlations between complex particles, the role played by collective motion and space-momentum correlations needs special considerations. By means of a semi-quantitative Monte Carlo approach, deuteron-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…To get a better measure of excitation of the fragmenting system the pre-equilibrium particles can be identified after BUU simulation at the freeze-out stage and can be taken out. In different multifragmentation experiments, it is observed that after pre-equilibrium emission around 75% to 80% of the total mass creates the fragmenting system [34][35][36]. To make it consistent with the other exiting works on the 112 Sn+ 112 Sn and 124 Sn+ 124 Sn reactions at 50 MeV/nucleon, we choose the test particles which create 75% of the total mass from the most central dense region.…”
Section: Basics Of the Modelmentioning
confidence: 99%
“…To get a better measure of excitation of the fragmenting system the pre-equilibrium particles can be identified after BUU simulation at the freeze-out stage and can be taken out. In different multifragmentation experiments, it is observed that after pre-equilibrium emission around 75% to 80% of the total mass creates the fragmenting system [34][35][36]. To make it consistent with the other exiting works on the 112 Sn+ 112 Sn and 124 Sn+ 124 Sn reactions at 50 MeV/nucleon, we choose the test particles which create 75% of the total mass from the most central dense region.…”
Section: Basics Of the Modelmentioning
confidence: 99%
“…These fit the category of preequilibrium emission. In different multifragmentation experiments, it is observed that after pre-equilibrium emission, 75% to 80% of the total mass creates the fragmenting system [23][24][25]. Hence we choose the test particles which create 80% of the total mass (i.e.…”
Section: Excitation Energy Determinationmentioning
confidence: 99%